Eksplorasi Dimensi-Dimensi Successful Aging - Fitria Ariani; Nur Syahadani Putri (Universitas Muria Kudus, 2023)
This research aims to describe the experiences of the dimensions of achieving successful aging experienced by the elderly. The dimensions of achieving successful aging are characterized by the fulfillment of the physical, psychological, cognitive, spiritual, social and financial dimensions. The method used in this research is a descriptive qualitative method using a case study approach. Data sources in this research consist of primary and secondary data sources. Primary data was set on an elderly person with the initials S who was 70 years old. The informant is a retired teacher (school principal). Data collection techniques were carried out through interviews and in-depth observations of informants and verified through source triangulation, namely the informant's children. The results of this research show that successful aging experienced by elderly people is not only based on satisfaction with themselves, family, environment and finances, but is also influenced by the way the elderly pass through their youth and the spiritual strength possessed by the elderly.